A leitura e seus impactos no rendimento do IDEB dos anos iniciais em Humaitá/AM - Santos, Gino Vieira dos (Brasil, 2021)
This course completion work was developed within the scope of the Pedagogy course at UFAM/IEAA, whose objective was to analyze the possible impacts of reading on the performance of the IDEB-Basic Education Development Index, from the early years in some public schools in the municipality. of Humaita-AM. The problem arose from some previous studies and projects, including the PIBIC of 2019/2020, when we investigated the possible relationship between reading and the impacts of IDEB on municipal public schools. The research took place through official data surveys from INEP-National Institute of Educational Studies and Research Anísio Teixeira, which present the ranking of quality of school education in the Brazilian context, in which the classification of schools appears, in addition to official data from INEP , online questionnaires were conducted (via Google form) with teachers who work in schools ranked as the highest and lowest IDEB in the municipality in order to verify the relationship between reading and the results obtained by the school in external evaluations. Thus, the research was developed from four topics: In the first topic, a retrospective of my memories in relation to my academic performance is presented in locus, where I present the experiences acquired in basic, elementary, secondary and higher education. This experience presents, in parts, my phases and real difficulties as a student, while acting in the classroom/, until I am literate by the teacher (a). In the second topic, reading and IDEB in school learning contexts are highlighted. The third topic deals with the paths that were used to carry out this study. The last topic comes to reflect on the reading and its possible impacts on IDEB's performance in the early years. It presents the results, pointing out that reading has been a determining factor in the high and low rates in external assessments in the two schools investigated.